Якість пилку Pinus pallasiana (Pinaceae) з насаджень екологічно безпечних і техногенно забруднених територій степової зони України - Коршиков, І.І.; Лаптєва, О.В. (Український ботанічний журнал, 2014)
Изучены фертильность, жизнеспособность, морфометрическая вариабельность пыльцы, встречаемость ее аномалий и отклонений в росте пыльцевых трубок у деревьев Pinus pallasiana D. Don из биосферного заповедника « Аскания-Нова» и трех насаждений г. Кривого Рога, произрастающих в зонах выбросов металлургических производств, а также на железорудном отвале. Жизнеспособность пыльцы во всех насаждениях была высокой, изменяясь в пределах 81,6—87,2 %. Более всего растения насаждений отличались по доле аномальной пыльцы и отклонениям в росте пыльцевых трубок при проращивании ее на 15 %-ной сахарозе. У деревьев заповедника этих аномалий было, соответственно, 7,9 % и 3,2 %, а у растений трех насаждений г. Кривого Рога — 13,2—24,8 % и 9,1—47,1 %. Fertility, viability, morphometric variability of pollen, occurrence of its anomalies and growth deviations of pollen tubes were studied in Pinus pallasiana D. Don of Biosphere Reserve «Askania-Nova» and three plantings from Kryvyi Rig, growing within the areas of emissions of metallurgical works (smolters), and also on the iron ore dump. The pollen viability was high in all of the plantations, being ranged from 81.6 to 87.2%. Trees from the plantations were mostly distinguished by their abnormal pollen percentages and deviating pollen tubes growth when germinated on 15 % saccharose. The rates of these anomalies were, respectively, 7.9 % and 3.2% in trees from the reserve, whereas they made 13.2 to 24.8 % and 9.1 to 47.1 % in trees from three Kryvyi Rig plantations.